Pengaruh Sistem Pengendalian Intern Pemerintah terhadap Laporan Keuangan Pemerintah Daerah Kabupaten Rote Ndao - Mali, Matheus Gratiano (POPULIKA, 2019)
This Research aims to  analyze the effect of implementation of Indonesia‟s Governmental Internal Control System called SPIP (Sistem Pengendalian Intern Pemerintah) based on the COSO Internal Control-fremawork, on the accountability of Local Government Financial Statements in Rote Ndao Distric. This Research aims to  described the very potential factors are affecting the implementation of Indonesia‟s Governmental Internal Control System, that causes desclaimer opinion on local government financial statements In Rote Ndao Distric, from Supreme Audit Board  Representatives of East Nusa Tenggara, since 2009 until 2013 and adverse opinion since 2014 until 2017. This is because the quality of the Local Government Financial Statements submitted does not meet the criteria for reliable, relevant, comparable and understandable. The Method of research uses a type of descriptive with a qualitative approach. Data was collected through interview, documentation and questionnaires. This research was conduct at Departmen Of Financial and Asset Management as report entity, The Inspektorat as Internal Control Apparatus Of Government.Findings of this research show that inhibiting factor in the application of this Government Internal Control System islack of commitment by the Regional Head and Leader of Department, and the lack of readiness of human resources of government apparatus, which needs serious attention both in quantity and quality of human resource management. Based on these findings it is recommended that the head of the government office is expected to increase awareness of the importance of internal control systems. It should also be constructed ongoing monitoring of the implementation of Governmental Internal Control System with enhancements to the audit, review, evaluation and other oversight activities